The Effect of Complex Acoustic Environment during Early Development on the Responses of Auditory Cortex Neurons in Rats - Pysanenko, Kateryna; Bureš, Zbyněk; Lindovský, Jiří; Syka, Josef (Neuroscience, 2018)
Acoustical environment plays an important role during the maturation of the auditory system. It has been shown that the sensory inputs to the developing centres influence the development of the structure of projections, neuronal responsiveness, excitatory-inhibitory balance, or tonotopical arrangement, throughout the auditory pathway. Our previous study (Bures et al., 2014) showed that rats reared in a complex acoustic environment (spectrally and temporally modulated sound reinforced by an active behavioural paradigm with a positive feedback) exhibit permanently improved response characteristics of the inferior colliculus (IC) neurons. Extending these results, the current work provides evidence that the changes occur also at the level of auditory cortex (AC). In particular, the enriched animals have lower excitatory thresholds, sharper frequency selectivity, and a lower proportion of non-monotonic rate-intensity functions. In contrast to the changes observed in the IC, the cortical neurons of enriched animals have lower response magnitudes. In addition, the enrichment changed the AC responsiveness to frequency-modulated and also to a lesser extent, amplitude-modulated stimuli. Significantly, the alterations span the entire hearing range and may be regarded as general and not directly linked to the characteristics of the acoustical stimulation. Furthermore, these developmentally induced changes are permanent and detectable in adulthood. The findings indicate that an acoustically enriched environment during the critical period of postnatal development influences basic properties of neuronal receptive fields in the AC, which may have implications for the ability to detect and discriminate sounds.
Keywords: Auditory Cortex; bydlení zvířat; Evoked Potentials, Auditory, Brain Stem; životní prostředí; Acoustic Stimulation; Environment; Female; Auditory Perception; Feedback; zvířata; neurony; sluchové kmenové evokované potenciály; Critical period; Rats, Long-Evans; Auditory cortex; Auditory Pathways; akustická stimulace; Enriched environment; ženské pohlaví; Neuronal receptive field; sluchová dráha; Neurons; Postnatal development; potkani Long-Evans; Animals; Membrane Potentials; membránové potenciály; sluchové korové centrum; sluchová percepce; Housing, Animal; zpětná vazba